Virtual Reality Training and Skill Enhancement for Offshore Workers - Sulaiman, S.B. (Institute of Electrical and Electronics Engineers Inc., 2020)
This project studies the application of virtual training environment for offshore workers. Working in the oil and gas industry where the technology is rapidly evolving results in the employee to perform tasks to current and new equipment. Many offshore workers require years of experience to obtain the relevant skills in handling with hazardous equipment. Due to the laid off experience workers, many companies are facing difficulty in training their new employee as most of them do not have enough training experience and are facing difficulty with adapting with the offshore environment. This virtual reality (VR) offshore training would provide a convenient training experience to the offshore workers in obtaining relevant machinery crane operating skills and operation in pipeline training. A simulator-based training using the Virtual Reality (VR) technology provides a more immersive training experience in a non-hazardous environment and can be perform in any closed room environment such in the office or at home. The training is programmed to monitor the workers performance based on the criteria evaluated will be recorded. The VR offshore training was conducted to a total of five users and the training was repeated for five times. A fifteen minutes rest was given in between each completed training. The percentage of user's achievement was recorded, and the results were tabulated. Â© 2020 IEEE.